Towards the development of an environmental curriculum for members of the planning professions - Long, Stanford Staples (Rhodes University, Faculty of Education, Department of Education, 1994)
In exercising their professional duties professional planners inevitably impact on the environment. In the past, more often than not, this impact has been allowed to occur without sufficient forethought, and usually to the detriment of the environment. In this research it is proposed that this undesirable state of affairs arises from inadequacies within the professional education of the planners, and that greater emphasis on the environmental education of planners is called for. From the perspective of a participative approach to curriculum development, the opinions of professional planners in the Port Elizabeth area were canvassed to establish baseline data in respect of their environmental education needs. To provide further information and a background against which the perceptions of the professional planners could be assessed, the opinions of the learned societies of the planning professions and of key environmentalists were also sought. In all these opinion surveys postal questionnaires formed the basis of the methodology employed. The extent of environmental education presently available to professional planners at tertiary institutions in South Africa and overseas, with particular emphasis on that available in the civil engineering discipline, was also investigated. The surveys revealed a strongly felt need for environmental education within the planning professions. The natural environment, the social environment, environmental ethics and interdisciplinary action all emerged as acceptable themes of the said education. A number of environmental topics to be covered were also identified. Block-release and part-time courses emerged as the most popular format for such environmental education offerings. The limited environmental education practice within the civil engineering discipline at South African tertiary institutions was noted, and the overseas practice in this regard provided useful insights. The data gathered as outlined above, formed the basis from which proposals towards an environmental curriculum for professional planners were made. Although these proposals focused primarily on the civil engineering discipline within the ambit of technikon-based educational programmes, wider multi-disciplinary applications remained an important concern. In the first instance, proposals aimed at expanding the environmental component of the existing first-qualification course were suggested. Secondly, proposals in respect of a post-first qualification, interdisciplinary, environmental study programme leading to a technikon degree were formulated.
Keywords: Ecology -- Policy; Education -- Environmental aspects; Curriculum planning -- South Africa